Educational Innovation in Islamic Education (PAI) with the TGT Learning Model Supported by Genially Media: Students' Learning Interest - Sari, Jihan Novita; Azizah, Nurul; Anwar, Syaiful; Murtadho, Ali; Syafe’i, Imam (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to examine the effectiveness of using a technology-based interactive learning model on students' learning interest. The learning model used in this research is Team Games Tournament (TGT), supported by Genially learning media, to measure its effectiveness on students' learning interest during the learning process. This research employs a quasi-experimental design with a post-test for both the experimental and control groups. The results of the study show that the t-test yielded a significance value of 0.21, indicating that there is a significant effectiveness in using the Team Games Tournament (TGT) learning model with Genially learning media to enhance students' learning interest. This study presents an innovation by combining the Team Games Tournament (TGT) learning model with Genially learning media to support students' interest in learning Islamic Education (PAI). The findings of this research can demonstrate how effective technology-based learning models are in improving the quality of education, which can serve as a consideration for education policymakers to better support the use of technology in the learning process, as well as provide training for teachers in utilizing interactive learning media to support a more effective learning experience.